Pengaruh Jangka Pendek dan Jangka Panjang Inflasi dan Suku Bunga BI Terhadap Harga Saham Dengan Metode Error Correction Model - Moulvi Dermawan; Tiar Lina Situngkir (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The purpose of the research is to analyze, know, and explain the short-term and long-term effects of Inflation and BI Interest Rates, both independently and simultaneously on the Stock Prices of Property, Real Estate and Construction Sector Companies listed on the Indonesia Stock Exchange for the period 2014-2023.The method used is a quantitative method with a descriptive verification approach with Error Correction Model (ECM) analysis, which is supported by Eviews 12 statistical software. The sampling technique utilizes purposive sampling technique, which then obtained 18 samples from 120 populations. The research results prove that in the short term and long term, inflation has no significant effect on stock prices. Then, the BI Interest Rate in the short term has no significant effect on stock prices, while in the long term the BI Interest Rate has a significant effect on stock prices. Simultaneously inflation and BI interest rates in the short term have no significant effect on stock prices. This is inversely proportional to the long-term results which prove that inflation and interest rates simultaneously have a significant effect on stock prices.